DETERMINANTS OF ECONOMIC GROWTH IN REGENCIES/CITIES OF BALI PROVINCE - I Dewa Ayu Nanda Widyaswari; Anak Agung Istri Ngurah Marhaeni (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2025)
Economic growth, besides being a reflection of economic conditions, is a basic element that supports social progress and the welfare of the population. This study aims to analyze (1) the differences in economic growth before, during, and after the pandemic in the regencies/cities of Bali Province, (2) the simultaneous effects of PAD, labor quality, investment, and technology utilization on economic growth in the regencies/cities of Bali Province, (3) the partial effects of local revenue, labor quality, investment, and technology utilization on economic growth in the regencies/cities of Bali Province, and (4) the role of technology utilization in moderating the effect of investment on economic growth in the regencies/cities of Bali Province. This study employs a quantitative approach. The number of observations in this research is 81. Data collection methods include observation and in-depth interviews. Data analysis techniques consist of descriptive statistics and inferential statistics (ANOVA and panel data regression analysis). The results show that (1) there are differences in economic growth before, during, and after the pandemic in the regencies/cities of Bali Province, (2) PAD, labor quality, investment, and technology utilization have a significant simultaneous effect on economic growth, (3) PAD, labor quality, and investment have a positive effect on economic growth in the regencies/cities of Bali Province, while technology utilization does not have a positive effect on economic growth, and (4) technology utilization does not moderate the effect of investment on economic growth in the regencies/cities of Bali Province.